Dual Method Use Among a Sample of First-Year College Women - Walsh, Jennifer L. (2014)
CONTEXT: Dual method use—using one type of contraceptive to reduce the risk of STDs and another to prevent pregnancy—is effective but understudied. No prior studies have employed an event-level approach to examining characteristics associated with dual method use among college women. METHODS: In 12 consecutive monthly surveys conducted in 2009–2010, data on 1,843 vaginal intercourse events were collected from 296 first-year college women. Women reported on their use of condoms and hormonal contraceptives during all events. Multilevel regression analysis was used to assess associations between event-, month- and person-level characteristics and hormonal use and dual method use. RESULTS: Women used hormonal contraceptives during 53% of events and condoms during 63%. Dual method use was reported 28% of the time, and only 14% of participants were consistent users of both methods. The likelihood of dual method use was elevated when sex partners were friends as opposed to romantic partners or ex-boyfriends, and among women who had received an STD diagnosis prior to college (odds ratios, 2.5–2.9); it also increased with level of religiosity (coefficient, 0.8). Dual use was less likely when less reliable methods were used (odds ratio, 0.2) and when women reported more months of hormonal use (0.8), were older (coefficient, −4.7) and had had a greater number of partners before college (−0.3). CONCLUSIONS: A better understanding of the characteristics associated with dual method use may help in the design of potential intervention efforts.